Synthesis, Characterization And Dna Cleavage Ability Of Cobalt(II) And Zinc(II) Complexes - Goh , Siu Mun (2010)
A total of ten cobalt(II) complexes and four zinc(II) complexes had been successfully synthesized between the reaction of cobalt(II)chloride hexahydrate, CoCl2.6H2O or zinc(II)acetate dihydrate, Zn(CH3COO)2.2H2O with carboxylic acids. Eight isostructural of complexes Co(II) and Zn(II) were formed by the reaction of CoCl2.6H2O or Zn(CH3COO)2.2H2O with pyrazine-2-carboxylic acid, maleic acid, 2-picolinic acid and malonic acid while the others six complexes were synthesized by the reaction of CoCl2.6H2O with glycine, glycolic acid, 3,-5dinitrobenzoic acid, quinolinic acid, pyridine-2,5-dicarboxylic acid and 4-aminobenzoic acid. These complexes were characterized by determination of melting point, conductivity measurement, Fourier Transform Infrared Spectroscopy (FT-IR), microanalysis CHN, Atomic Absorption Spectroscopy (AAS), Cyclic Voltammetry (CV), Thermogravimetry Analysis (TGA) and X-ray Crystallograhy. While the biological properties of these complexes were determined by DNA Cleavage and MTT Assay. From the FT-IR analysis, all the ligands coordinated the atoms Co(II) and Zn(II) in monodentate. While from UV-Vis analysis, the oxidation state of the cobalt(II) complexes were in +2 and showed d-d transition peaks corresponding to d7 system while the oxidation state of zinc(II) complexes were also +2 and in d10 system.